A novel multiplex real-time PCR for the identification of mycobacteria associated with zoonotic tuberculosis. - Kate Reddington (Public Library of Science (PLoS), 2011)
Background Tuberculosis (TB) is the leading cause of death worldwide from a single infectious agent. An ability to detect the Mycobacterium tuberculosis complex (MTC) in clinical material while simultaneously differentiating its members is considered important. This allows for the gathering of epidemiological information pertaining to the prevalence, transmission and geographical distribution of the MTC, including those MTC members associated with zoonotic TB infection in humans. Also differentiating between members of the MTC provides the clinician with inherent MTC specific drug susceptibility profiles to guide appropriate chemotherapy. Methodology/principal findings The aim of this study was to develop a multiplex real-time PCR assay using novel molecular targets to identify and differentiate between the phylogenetically closely related M. bovis, M. bovis BCG and M. caprae. The lpqT gene was explored for the collective identification of M. bovis, M. bovis BCG and M. caprae, the lepA gene was targeted for the specific identification of M. caprae and a Region of Difference 1 (RD1) assay was incorporated in the test to differentiate M. bovis BCG. The multiplex real-time PCR assay was evaluated on 133 bacterial strains and was determined to be 100% specific for the members of the MTC targeted. Conclusions/significance The multiplex real-time PCR assay developed in this study is the first assay described for the identification and simultaneous differentiation of M. bovis, M. bovis BCG and M. caprae in one internally controlled reaction. Future validation of this multiplex assay should demonstrate its potential in the rapid and accurate diagnosis of TB caused by these three mycobacteria. Furthermore, the developed assay may be used in conjunction with a recently described multiplex real-time PCR assay for identification of the MTC and simultaneous differentiation of M. tuberculosis, M. canettii resulting in an ability to differentiate five of the eight members of the MTC.